Comparison of the effect of vitamin C and selenium nanoparticles on gentamicin-induced renal impairment in male rats: a biochemical, molecular and histological study. (4th May 2023) - Zheng, Su; Hameed Sultan, Afrah; Kurtas, Prshng Tofiq; Kareem, Layla Abdulsattar; Akbari, Abolfazl
Abstract: Renal failure caused by gentamicin is mainly mediated through oxidative damage, inflammation, and apoptosis. Hence, vitamin C and selenium, which have antioxidant, anti-inflammatory, and anti-apoptotic properties, and their nanoparticle forms, which have recently received attention, may reduce gentamicin-induced side effects. Therefore, the aim of this study was to investigate the therapeutic effects of vitamin C and selenium, and their nanoparticles on gentamicin-induced renal damage in male rats. 128 adult male Wistar rats were randomly divided into equal sixteen controlled and treated groups. Serum levels of uric acid, blood urea nitrogen, urea, and creatinine were measured. Renal levels of oxidative parameters such as MDA, SOD, and CAT and inflammatory parameters including IL-1β, and TNF-α were measured. Renal expression of Nrf2, NF-κB, Bcl-2, caspase-3, BAX and mTORc1 was also evaluated. The results showed that gentamicin causes oxidative damage, inflammation, apoptosis and disruption of autophagy in kidney tissue in a dose-dependent manner. However, treatment with vitamin C, selenium and their nanoparticles could significantly improve these effects. Also, the results showed that the inflammatory and oxidative parameters and the expression of genes involved in them and apoptosis in the gentamicin groups treated with vitamin C nanoparticles and selenium nanoparticles reduced significantly compared to those treated with vitamin C and selenium. It can be concluded that vitamin C, selenium and their nanoparticles can improve gentamicin-induced kidney damage by inhibiting oxidative damage, inflammation and apoptosis-induced by autophagy, and can be a good option for kidney damage caused by gentamicin or as an adjunctive treatment to reduce its side effects.